Overview on drug utilisation research in developing countries: issues & challenges - Abdul Razak, Dzulkifli (2019)
To provide clinical guidance to the Commissioner regarding the utilization of pharmaceuticals and the evaluation of drug expenditures within the Medicaid program. The activities include but are not limited to the following: establishment and implementation of medical standards and criteria for the prospective and retrospective DUR program, development, selection, application, and assessment of educational interventions for physicians, pharmacists and recipients that improve care, administration of pharmacy programs, [and to implement consistent management strategies,] including the Preferred Drug Program and the Clinical Drug Review Program, and evaluation of drugs which may be responsible for exceeding the budgetary drug cap.